Hipoteca reversa - Marcelo Caetano; Daniel Da Mata (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper describes the main characteristics of reverse mortgage and it also assesses the main aspects related to its implementation in Brazil. A reverse mortgage is an equity release product that allows old people to convert their housing asset into an income flow, without the requirement of selling their house, making regular payments or losing the housing tenure. In other words, reverse mortgages aim to generate income to old people without losing the right to live in their houses. Reverse mortgage is a loan category against the house without requirement of regular payments. Mortgage proceeds can be paid as a lump sum, as regular monthly payments, as a credit line, or as a combination of the former alternatives. This paper describes reverse mortgage and its categories; it also states the usual aims and risks of a reverse mortgage. Furthermore, this article measures the potentialities for reverse mortgage in Brazil and it also presents an international comparison for this product.
Keywords: G21; G28; H55; R31; 330; Umkehrhypothek; Altersvorsorge; Brasilien